Decision making for nursing rehabilitation in intensive care: foci of care - Prazeres, Virgínia Maria Pereira (2021)
Objective: to understand the focus of care developed by nurses specialized in adult intensive care rehabilitation. Methods: qualitative study with a focus group session with six nurses, specialists in rehabilitation nursing, who have roles in the intensive care of three hospitals. The information transcribed was submitted to content analysis. Results: regarding the profile of participants, three were female and three were male, with ages varying from 28 to 51 years old, with a mean of 39.33 years old (standard deviation=7.32). Through data analysis, two categories emerged: Sedated Clients and Awake Clients. Conclusion: when the client was sedated, the care was focused on the processes of the respiratory and musculoskeletal systems that were compromised. When he was awake, more elements related to those body processes became foci of care, in addition to other elements related to the psychological process, to the phenomenon of status, and to self-care.